Identification and characterization of pesticide metabolites in Brassica species by liquid chromatography travelling wave ion mobility quadrupole time-of-flight mass spectrometry (UPLC-TWIMS-QTOF-MS). (1st April 2018) - Bauer, Anna; Luetjohann, Jens; Hanschen, Franziska S.; Schreiner, Monika; Kuballa, Jürgen; Jantzen, Eckard; Rohn, Sascha
Highlights: Development of an UPLC-TWIMS-QToF MS method for metabolite detection in plant matrices. Degradation pathways of thiacloprid, azoxystrobin, and difenoconazole in Brassica species. Identification of multiple phase I and II pesticide metabolites. Analysis of pesticide metabolite fingerprints in individual plant organs. Abstract: A new mass spectrometric method for evaluating metabolite formation of the pesticides thiacloprid, azoxystrobin, and difenoconazole was developed for the Brassica species pak choi and broccoli. Both, distribution and transformation kinetics of the active compounds and their metabolites were analyzed by UPLC-TWIMS-QTOF-MS. Additionally, HR-MS analysis and structure elucidation tools such as diagnostic ions, isotopic matches, and collision cross sections were applied for metabolites identification. Following the application of two plant protection products (containing the above-mentioned active compounds) in a greenhouse study plant material was cryo-milled and extracted with water/methanol. The residual levels of active compounds were identified at certain timepoints during pre-harvest intervals and in the final products. Different phase I and phase II metabolites of the pesticides were identified in different plant organs such as leaves, stems, (broccoli) heads, and roots. Three individual degradation pathways and distribution profiles are suggested including eight thiacloprid, eleven azoxystrobin and three difenoconazole metabolites.